Multifractal characterization of a dental restorative composite after air-polishing. (February 2015) - Ţălu, Ştefan; Stach, Sebastian; Alb, Sandu Florin; Salerno, Marco
Abstract: Roughness is of critical importance for the surface of dental materials. Air-polishing is a procedure commonly used on dental surfaces to remove the biofilm, however it can also damage the material surface. As a result its roughness is increased, and the possible fractal dimension, if any, may change. This study reviews atomic force microscope images of a reference dental restorative composite, treated with abrasive powders of either sodium bicarbonate or glycine, for times of 5, 10 or 30 s, and from distances of 2 or 7 mm. To fully characterize the structural complexity of surface damage, the images were analyzed according to both statistical parameters and multifractal approach. The singularity spectrum f ( α ) provided quantitative values data to characterize the local scale properties of 3D surface geometry at nanometer scale. The lowest roughening of the surfaces was obtained by air-polishing with glycine for 5 s, independent of the used distance. This observation of least damage and thus best treatment was confirmed by the multifractal analysis. Multifractal analysis provides quantitative information complementary to that offered by traditional surface statistical parameters, with great potential for use also in the field of examination of quality of dental material surfaces.